2019
DOI: 10.1186/s12947-019-0175-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implication of disturbed left atrial phasic functions in the heterogeneous population associated with hypertension or atrial fibrillation

Abstract: Background: To evaluate left atrial (LA) phasic functions in patients with hypertension and/or paroxysmal atrial fibrillation (PAF) and its clinical significance. Methods: LA strain was studied in 77 patients (25 hypertension, 24 lone AF, and 28 with both hypertension and PAF) and 28 controls using two-dimensional speckle-tracking echocardiography (2D STE). The following indexes during atrial reservoir, conduit and pump phase were analyzed respectively: (1) peak atrial longitudinal strain (PALS) and strain rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
5
0
1
Order By: Relevance
“…Similar results have been found in other cardiovascular diseases, but so far there has been no such study conducted on patients with AS. Recently published data have demonstrated similar associations between LV systolic dysfunction and LA enlargement and impairment [9,33]. Moreover, in our diseased group, LVEF deterioration was closely related to LA dysfunction, similar to other reports [34].…”
Section: The Ability Of La Parameters To Predict Composite Endpoint I...supporting
confidence: 92%
“…Similar results have been found in other cardiovascular diseases, but so far there has been no such study conducted on patients with AS. Recently published data have demonstrated similar associations between LV systolic dysfunction and LA enlargement and impairment [9,33]. Moreover, in our diseased group, LVEF deterioration was closely related to LA dysfunction, similar to other reports [34].…”
Section: The Ability Of La Parameters To Predict Composite Endpoint I...supporting
confidence: 92%
“…Time to event analysis showed significant predictive ability, especially for those with severe impairment of LA-ε t (third tertile; LA-ε t < 30%). The predictive role of LA strain had been previously shown in both echocardiography and CMR studies, in other cardiovascular diseases [ 12 , 31 , 38 , 40 ]. To date, this is the first study to prove the predictive ability of LA-ε t in NIDCM.…”
Section: Discussionmentioning
confidence: 92%
“…First and foremost, studies that analyzed the role of echocardiography in LA remodelling, phasic function and geometry have begun to emerge. They had shown that LA phasic function parameters were strongly associated with HF, impaired LV relaxation and compliance, atrial fibrillation and AHT [ 10 , 20 , 31 , 32 , 33 ]. LA conduit function was found to be defective even before LV hypertrophy and enlargement occurred [ 34 ], and to be directly associated with diastolic dysfunction, its severity [ 32 ] and progression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LA reservoir strain is a highly sensitive marker of LV DD and decreases linearly with worsening LV DD 14–17. A negative correlation between BP indices and left trial strain (LAS) is seen in other populations 18–20. Given that children with SCD are at-risk for DD, the assessment of diastolic function using LA mechanics is important.…”
mentioning
confidence: 99%